POLA KOMUNIKASI ANTAR PEMAIN MOBILE LEGENDS : BANG BANG USIA DEWASA MUDA DI KOTA MADIUN - Nayottama, Fuad Fajar Nayottama; Widiantari, Maria M; Sejati, Veny Ari (Universitas Pahlawan Tuanku Tambusai, 2025)
Mobile Legends: Bang Bang (MLBB) has become a popular phenomenon among Generation Z in Madiun City, serving not only as entertainment but also as a medium for building social relationships. Communication among MLBB players tends to be cooperative and supportive, although it can also be aggressive at times. This study aims to explore the patterns of verbal and nonverbal communication among young adult MLBB players in Madiun. The research uses a descriptive qualitative method, based on DeVito’s interpersonal communication theory and Walther’s Computer-Mediated Communication (CMC) theory. The results show that verbal communication patterns are dynamic and creative, utilizing in-game chat, voice chat, and special slang terms such as